Taxes and the Price Level : A Further Examination of the PPP Hypothesis - Kleiman, Ephraim (IMF Working Papers; Working Paper, 1993)
The effects of taxation on the general price level have traditionally been regarded as reflecting monetary policy, rather than fiscal factors. This view abstracted from the possible endogeneity of monetary expansion with respect to tax hikes, and from the effects which taxation may have on the reserve price of entrepreneurial labor. An analysis of Purchasing Power Parity data for 51 countries from stage IV of the ICP project supports the hypothesis that domestic indirect taxes tend to raise the general price level. In contrast to the accepted view, other prices do not seem to decline to offset the effect of such taxes on the price of tradables. The paper also presents some new evidence on the other factors which cause national price levels to diverge from PPP.